Analysis of Ultrasonic Pulse Veocty Method Effeciency On RC Column Bonded With Lightning Protection System. - Wan Muhamad Aiman Wan Atan (School of Environmental Engineering, University Malaysia Perlis, 2016)
The objectives of study that have been focused in this research study are summarized as below to analyst the performance on the concrete structure influence by lightning protection system cable bounded with the reinforcement concrete column. To determine the influence of existing rebar in column on Ultrasonic Pulse Velocity (UPV) test result. To determine the influence of transducers spacing and arrangement location at column via UPV test result.